2022
DOI: 10.1021/acs.jafc.2c05334
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Metabolism of Pterostilbene, a Dietary Resveratrol Derivative: Metabolite Identification, Species Differences, Isozyme Contribution, and Further Bioactivation

Abstract: Pterostilbene (PTE), a dietary derivative of resveratrol, displayed pleiotropic health-promoting activities. This study aimed to explore the metabolic profiles and species differences of the phase I metabolism of PTE and to investigate subsequent detoxification after PTE bioactivation. PTE was found to be biotransformed to two pharmacologically active metabolites, pinostilbene and 3′-hydroxypterostilbene, in vivo and in vitro with substantial species differences. Human CYP1A2 was proved to be mainly responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous research has demonstrated that compound 8 possesses better pharmacokinetic properties, and our current study revealed that it exhibited inhibitory effects on V30M-TTR fibrillization comparable to 1 . Our results also indicated that pinostilbene ( 7 ), a pharmacologically active metabolite of 8 , possessed potent inhibitory potency against V30M-TTR fibrillization . These results suggest that further research is warranted toward the practical applications of 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that compound 8 possesses better pharmacokinetic properties, and our current study revealed that it exhibited inhibitory effects on V30M-TTR fibrillization comparable to 1 . Our results also indicated that pinostilbene ( 7 ), a pharmacologically active metabolite of 8 , possessed potent inhibitory potency against V30M-TTR fibrillization . These results suggest that further research is warranted toward the practical applications of 8 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Our results also indicated that pinostilbene (7), a pharmacologically active metabolite of 8, possessed potent inhibitory potency against V30M-TTR fibrillization. 37 These results suggest that further research is warranted toward the practical applications of 8.…”
Section: ■ Discussionmentioning
confidence: 99%
“…PTS undergoes significant first-pass metabolism in the liver, which is vital for its systemic clearance. This metabolism primarily involves phase II detoxification reactions, predominantly glucuronidation, and sulfation, transforming PTS into more water-soluble forms suitable for excretion ( Kapetanovic et al, 2011 ; Gómez-Zorita et al, 2021 ; Li et al, 2023 ). Compared to RSV, PTS has a much lower glucuronidation efficiency in the liver, affecting its human metabolism ( Dellinger et al, 2014 ).…”
Section: Metabolism Of Pterostilbenementioning
confidence: 99%
“…It also has analgesic, antiaging, antidiabetic, anti-inflammatory, antiobesity, antioxidant, cholesterol-lowering, and neuroprotective properties [25]. Moreover, it depicts higher biological activity, stability, and bioavailability [26]. Pan, J. et al found that pterostilbene is the bioactive component of the blueberry, which reduced serum uric acid and protected the kidneys in hyperuricemic nephropathy (HN) mice by reducing the serum creatinine, urea, urinary albumin, and urinary albumin to creatinine ratio (u-ACR) [27].…”
Section: Introductionmentioning
confidence: 99%